Extracting high-quality DNA and PCR amplification from anuran skin (Bornean toads) - Sharizzaty, binti Mohd Rais (Universiti Malaysia Sarawak (UNIMAS), 2012)
The modified DNA extraction protocol of anuran skin was determined by using mitochondrial DNA from cytochrome oxidase I (COI) gene. There were nine species of 44 individuals comprising two family of anurans; family Bufonidae that comprised genera Phrynoidis, Pesdostibes, Ingerophrynus, Dutthaphrynus and Ansonia and family Ranidae were included in this study. Specimen were collected from eight localities in Sarawak including Universiti Malaysia Sarawak Campus (UNIMAS),Kubah National Park, Gading National Park, Bako National Park, Mount Santubong, Mount Jagoi, Annah Rais (Padawan) and Batang Ai National Park. In this study, cytochrome oxidase 1 (COI) of mitochondrial gene was used to investigate suitable parameters in amplifying PCR products for skin sampled. The annealing temperature for these selected species ranges from 50 - 63 based on the optimization. From this study, concluded that the modified DNA CTAB extraction protocol was useful to extracting DNA from anuran skin.